Counselling education for speech-language pathology students in Australia: a survey of education in post-stroke aphasia. Issue 12 (2nd December 2022) - Sekhon, Jasvinder, K; Oates, Jennifer; Kneebone, Ian; Rose, Miranda L
ABSTRACT: Background: Speech-language pathology practice guidelines recommend competency in counselling to support psychological adjustment and well-being in people with communication disability. However, there is limited information about what counselling education speech-language pathology students need or receive to attain this competency. Speech-language pathologists report that they frequently use counselling to support psychological well-being in people with post-stroke aphasia, a patient group particularly vulnerable to mood disorders, but they also report low knowledge, skill, and confidence in this practice. We aimed to describe the content, methods, duration, and evaluation of counselling education currently offered to Australian speech-language pathology students, including education specifically aimed at supporting the psychological well-being of people with post-stroke aphasia. Methods and Procedures: Directors of all accredited speech-language pathology programs (N = 21) across 15 eligible Australian Universities were invited to participate in an online survey. Outcomes and Results: Responses from 12 of the 21 eligible (57%) programs were obtained. Ten programs (83%) reported offering counselling education with four programs (33%) offering this specifically for people affected by post-stroke aphasia. Most programs provided over 10 hours of counselling coursework but provided less than 3 hours of counselling observation and practicum. Teaching on a variety of counselling topics was reported, most commonly general principles of counselling, while specific approaches included motivational interviewing and cognitive behavioural therapy. Counselling was taught using a range of methods, most frequently problem-based learning and role-play. Student counselling knowledge, skills, and competence were evaluated by written assignment, review of video/written transcripts of role-play, oral presentation, and problem-based learning (case studies) group discussion. Academics had mixed opinions on graduate competency for counselling. Conclusions: While the majority of university programs reported providing counselling education, few offered education to support the psychological needs of people specifically affected by post-stroke aphasia. Some courses offered no counselling education. Minimum standards of counselling education for speech-language pathology students are required to ensure graduates are competent to provide counselling to support adjustment and well-being in people with communication disabilities.